Pengaruh Kemampuan Digital, Ekosistem Kewirausahaan Digital dan Efikasi Diri Terhadap Niat Berwirausaha Digital - Muyassaroh Muyassaroh; Aflit Nuryulia Praswati (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The rapid development of digital technology has created new opportunities for technology-based entrepreneurship, particularly among university students as a generation highly adaptable to digital transformation. However, differences in individual readiness to pursue digital entrepreneurship remain evident, especially in terms of digital capabilities, environmental support, and self-confidence. This study aims to analyze the effect of digital capability, digital entrepreneurial ecosystem, and self-efficacy on digital entrepreneurial intention among university students. This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to student respondents and analyzed using multiple linear regression analysis. The results indicate that digital capability, digital entrepreneurial ecosystem, and self-efficacy each have a positive and significant effect on digital entrepreneurial intention. Furthermore, these variables simultaneously have a significant influence on students’ digital entrepreneurial intention. The findings highlight the importance of enhancing digital skills, strengthening the digital entrepreneurial ecosystem, and developing self-efficacy to encourage the growth of digital entrepreneurial intention among students. This study is expected to contribute to the development of entrepreneurship education and provide insights for policymakers in fostering a sustainable digital entrepreneurship ecosystem.